2019
DOI: 10.1007/s12178-019-09545-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Sports-Related Concussion

Abstract: Purpose of Review Here, we summarize the current scientific literature on the management of sports-related concussion (SRC) in the acute period (< 6 weeks post-injury) with a focus on rest, return to learn, return to play, and emerging treatments. Recent Findings While relative rest is recommended for the first 24-48 h following acute SRC, the most recent guidelines highlight the lack of evidence for complete rest and in fact show that prolonged cognitive and physical rest can be detrimental. Gradual return to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Current treatment strategies for depression, anxiety and fear/PTSD in brain-injured patients utilize best practices that are in place for treating these disorders in patients that have not suffered a TBI ( Plantier and LuautĂ©, 2016 ; Gupta et al, 2019 ; Silverberg and Panenka, 2019 ). Thus, serotonin reuptake inhibitors (SSRIs) are the most utilized therapy for post-traumatic depression ( Kraus et al, 2017 ; Silverberg and Panenka, 2019 ).…”
Section: Current Treatment Strategies For Post-traumatic Affective DImentioning
confidence: 99%
“…Current treatment strategies for depression, anxiety and fear/PTSD in brain-injured patients utilize best practices that are in place for treating these disorders in patients that have not suffered a TBI ( Plantier and LuautĂ©, 2016 ; Gupta et al, 2019 ; Silverberg and Panenka, 2019 ). Thus, serotonin reuptake inhibitors (SSRIs) are the most utilized therapy for post-traumatic depression ( Kraus et al, 2017 ; Silverberg and Panenka, 2019 ).…”
Section: Current Treatment Strategies For Post-traumatic Affective DImentioning
confidence: 99%
“…The perfect time to return to sport (RTS) after having an SRC is a highly discussed topic [ 15 , 29 , 42 , 44 , 45 , 46 ]. Each patient has to be treated individually by a step-by-step return to sport protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In most recommendations, adequate rest is the main principle of treatment. Taking a break until concussion signs fade seems to be the best way to avoid the prolongation of symptoms so far [ 31 , 45 ], even if recent studies showed a converse thesis and demonstrated a reduced rate of PCS and a faster rehabilitation process after a shorter break, as well as an early beginning of moderate training [ 47 , 48 ]. Light aerobic exercise with cervical, vestibular, cognitive behavioral or vision therapy is also discussed as a potentially positive influence on returning to sport [ 46 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of variance showed significant differences in the degree of depression among the elderly in different living environments. 8 The depression in public places was the lowest, and the depression in hospitals was the highest.…”
Section: The Impact Of Different Living Environments On the Degree Of Depression In The Elderlymentioning
confidence: 99%